Introduction - Brown, Ashley; Bidarra, Rafael (Transactions of the Digital Games Research Association, 2017)
In 2016, for the first time, the Digital Games Research Association (DiGRA) and the Society for the Advancement of the Science of Digital Games (SASDG) partnered and decided to jointly host an unprecedented gathering of game-related researchers. The result was the largest ever academic conference on games research: the 1st JOINT INTERNATIONAL CONFERENCE OF DIGRA AND FDG.